Kidney disease pathways, options and decisions: an environmental scan of international patient decision aids. Issue 12 (23rd August 2020) - Winterbottom, Anna E; Mooney, Andrew; Russon, Lynne; Hipkiss, Vicki; Ziegler, Lucy; Williams, Richard; Finderup, Jeanette; Bekker, Hilary L
Abstract: Background: Conservative management is recognized as an acceptable treatment for people with worsening chronic kidney disease; however, patients consistently report they lack understanding about their changing disease state and feel unsupported in making shared decisions about future treatment. The purpose of this review was to critically evaluate patient decision aids (PtDAs) developed to support patient–professional shared decision-making between dialysis and conservative management treatment pathways. Methods: We performed a systematic review of resources accessible in English using environmental scan methods. Data sources included online databases of research publications, repositories for clinical guidelines, research projects and PtDAs, international PtDA expert lists and reference lists from relevant publications. The resource selection was from 56 screened records; 17 PtDAs were included. A data extraction sheet was applied to all eligible resources, eliciting resource characteristics, decision architecture to boost/bias thinking, indicators of quality such as International Standards for Patient Decision Aids Standards checklist and engagement with health services. Results: PtDAs were developed in five countries; eleven were publically available via the Internet. Treatment options described were dialysis ( n = 17), conservative management ( n = 9) and transplant ( n = 5). Eight resources signposted conservative management as an option rather than an active choice. Ten different labels across 14 resources were used to name 'conservative management'. The readability of the resources was good. Six publications detail decision aid development and/or evaluation research. Using PtDAs improved treatment decision-making by patients. Only resources identified as PtDAs and available in English were included. Conclusions: PtDAs are used by some services to support patients choosing between dialysis options or end-of-life options. PtDAs developed to proactively support people making informed decisions between conservative management and dialysis treatments are likely to enable services to meet current best practice.